Literatura rosyjska na łamach biuletynu Instytutu Naukowo-Badawczego Europy Wschodniej w Wilnie , Balticoslavica”(1933-1938) - Zienkiewicz, Tadeusz (Acta Polono-Ruthenica, 2006)
Institute of Eastern Europe in Vilnius was established in 1930 and worked till 1939. Its an elementary assignment was collecting and working up with research materials concerning to economy, history, folkloristic and philology of Polish eastern neighbors, mainly Soviet Union. The literature from humanistic area of interest had been published in Bulletin „Balticoslavica”. The literature was a main topic of these publications. The authors of articles, critiques, and bibliographic notes, focus on literary and scientific life by review of publications in many countries, including Germany, Soviet Union, Estonia, Finland, Czechoslovakia, Yugoslavia, France and many more. Especially, lot of attention and comments was connected to articles concerned with Russian literature - theory, poetry, drama, prose; this problem is a topic of present essay.